Urease Inhibition and Structure‐Activity Relationship Study of Thiazolidinone‐, Triazole‐, and Benzothiazole‐Based Heterocyclic Derivatives: A Focus Review. Issue 13 (3rd April 2023) - Singh, Rahul; Kumar, Parvin; Devi, Meena; Sindhu, Jayant; Kumar, Ashwani; Lal, Sohan; Singh, Devender; Kumar, Harish; Kumar, Sumit
Abstract: Urease has a long and distinguished history in the development of enzymology since it was the first enzyme crystallized by Sumner in 1926. The present review article is focused on the urease inhibitory potential of thiazolidinone, triazole, and benzothiazole‐based heterocyclic derivatives. The study begins with the historical developments in the discovery of urease and its substrate, urea, along with the active site architecture of ureases of different origins. The two pathways for the urease‐catalyzed hydrolysis of urea are explained in detail. The urease inhibitory potential of the aforementioned heterocyclic derivatives is reviewed and arranged systematically. Structure‐activity relationships (SARs) study provided the substituents necessary for urease inhibition and will be useful for the researchers working in the field of anti‐ulcer agents. To a step further, important binding interactions were identified with the amino acid residues at the active site of the enzyme. The information gathered is anticipated to offer logical direction and an effective method for creating innovative, potent, and efficient urease inhibitors that will have greater practical uses in the future. Abstract : In recent years, the impact of urease on humans, animals as well as in agriculture has been recognized as a substantial target in research. This article presents urease inhibition by heterocyclic compounds having thiazolidinone, benzothiazole, and triazole scaffolds with a focus on structural fragments that leads to the development of potent urease inhibitors.